Pengenalan Agropreneur melalui Budidaya Tanaman Hidroponik di SDN 02 Patrang, Jember - Ubaidillah, Mohammad; Karyaningtyas, Setyowati; Suud, Hasbi mubarak; Kumala, Velliana Dhea; Misi, Dina Aulia; Novita, Septian Abelia; Maharani, Adinda Putri; Jayanti, Silvi Dwi; Suryalaksono, Kemal Beryl; Puspito, Agung Nugroho (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research aims to increase students awareness of the environment through hydroponic cultivation at SDN 2 Patrang Jember. This research uses qualitative methods with observation, interviews and document analysis. The research results show that hydroponic cultivation at SDN 2 Patrang Jember has succeeded in increasing students' environmental awareness and knowledge about agriculture. This research also shows that hydroponic cultivation can be an effective alternative in increasing environmental awareness, as well as contributing to the development of environmentally caring character in students. Thus, this research can be a reference for other schools in developing effective greening programs in increasing environmental awareness in students.